Boundary Liouville Theory: Hamiltonian Description and Quantization - Dorn, H.; Jorjadze, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
The paper is devoted to the Hamiltonian treatment of classical and quantum properties of Liouville field theory on a timelike strip in 2d Minkowski space. We give a complete description of classical solutions regular in the interior of the strip and obeying constant conformally invariant conditions on both boundaries. Depending on the values of the two boundary parameters these solutions may have different monodromy properties and are related to bound or scattering states. By Bohr-Sommerfeld quantization we find the quasiclassical discrete energy spectrum for the bound states in agreement with the corresponding limit of spectral data obtained previously by conformal bootstrap methods in Euclidean space. The full quantum version of the special vertex operator e-φ in terms of free field exponentials is constructed in the hyperbolic sector.